Determinación del índice de vulnerabilidad sísmica de las viviendas existentes en el barrio 24 de mayo de la ciudad de Riobamba - Alvarado Uvidia, Nelly Verónica (2014)
Advances made by the Structural Engineering in the study of the behavior of buildings with a seismic event, soil structure interaction, represented for many institutions nationwide starting point for the evaluation of seismic vulnerability, may determine the vulnerability index in an approximate form of a house in an earthquake.